Digital Religious Services: Analysis of Religious Fusion and Entertainment in the Short Film Cerita Hijrahku - Al Jufri, Muhammad Arman; Ar, Muhammad Syafi’i As’ad (UIN Sunan Ampel Surabaya, 2022)
This article discusses the presence of new religious digital services reflected in the Muslim inspiration film